Oral mucosal health in liver transplant recipients and controls. Issue 1 (12th December 2013) - Helenius‐Hietala, Jaana; Ruokonen, Hellevi; Grönroos, Lisa; Rissanen, Harri; Vehkalahti, Miira M.; Suominen, Liisa; Isoniemi, Helena; Meurman, Jukka H.
<x xml:space="preserve">Abstract</x> Immunosuppressive drugs and other medications may predispose patients to oral diseases. Data on oral mucosal health in recipients of liver transplantation (LT) are limited. We, therefore, recruited 84 LT recipients (64 with chronic liver disease and 20 with acute liver failure) for clinical oral examinations in a cross‐sectional, case‐control study. Their oral health had been clinically examined before transplantation. The prevalence of oral mucosal lesions (OMLs) was assessed in groups with different etiologies of liver disease and in groups with different immunosuppressive medications, and these groups were compared to controls selected from a nationwide survey in Finland (n = 252). Risk factors for OMLs were evaluated with logistic regression. OMLs were more frequent in LT recipients versus controls (43% versus 15%, P < 0.001), and the use of steroids raised the prevalence to 53%. Drug‐induced gingival overgrowth was the single most common type of lesion, and its prevalence was significantly higher for patients using cyclosporine A (CSA; 29%) versus patients using tacrolimus (TAC; 5%, P = 0.007); the prevalence was even higher with the simultaneous use of calcium channel blockers and CSA (47%) or TAC (8%, P = 0.002). Lesions with malignant potential such as drug‐induced lichenoid reactions, oral lichen planus–like lesions, leukoplakias, and ulcers occurred in 13% of the patients with chronic liver disease and in 6% of the controls. Every third patient with chronic liver disease had reduced salivary flow, and more than half of all patients were positive for Candida; this risk was higher with steroids. In conclusion, the high frequency of OMLs among LT recipients can be explained not only by immunosuppressive drugs but also by other medications. Because dry mouth affects oral health and OMLs may have the potential for malignant transformation, annual oral examinations are indicated. Liver Transpl 20:72–80, 2014. © 2013 AASLD.